A multi-target caffeine derived rhodium(I) N-heterocyclic carbene complex: evaluation of the mechanism of action - Zhang, Jing-Jing; Muenzner, Julienne K.; Maaty, Mohamed A. Abu el; Karge, Bianka; Schobert, Rainer; Wölfl, Stefan; Ott, Ingo (Dalton transactions, 2016)
A rhodium(I) and a ruthenium(II) complex with a caffeine derived N-heterocyclic carbene (NHC) ligand were biologically investigated as organometallic conjugates consisting of a metal center and a naturally occurring moiety. While the ruthenium(II) complex was largely inactive, the rhodium(I) NHC complex displayed selective cytotoxicity and significant anti-metastatic and in vivo anti-vascular activities and acted as both a mammalian and an E. coli thioredoxin reductase inhibitor. In HCT-116 cells it increased the reactive oxygen species level, leading to DNA damage, and it induced cell cycle arrest, decreased the mitochondrial membrane potential, and triggered apoptosis. This rhodium(I) NHC derivative thus represents a multi-target compound with promising anti-cancer potential.
Gesehen am 04.10.2021